Preparation of a double-network hydrogel based on wastepaper and its application in the treatment of wastewater containing copper(ii) and methylene blue. Issue 29 (19th May 2021) - Chen, Yaoning; Li, Linshenzhang; Li, Yuanping; Liu, Yihuan; Chen, Yanrong; Li, Hui; Li, Meiling; Xu, Fangting; Liu, Yuqing
Abstract : In this research, wastepaper was innovatively compounded with acrylamide to prepare a wastepaper/acrylamide double-network hydrogel and was applied to the treatment of the mixed wastewater containing copper(ii ) and methylene blue. Abstract : To reclaim and utilize wastepaper (WP), a WP/acrylamide double-network hydrogel (WP/PAM) was prepared to transform WP into efficient adsorbent for heavy metals and dye wastewater treatment. The structure and properties of the WP/PAM were characterized systematically by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), swelling performance (SR), Fourier transform infrared spectrum (FTIR), and X-ray photoelectron spectroscopy (XPS). Batch experiments showed that the adsorption process of Cu(ii ) and MB followed the pseudo-second-order kinetic model and the Langmuir model. The maximum adsorption capacities of the WP/PAM for Cu(ii ) and MB were 142.2 mg g −1 and 1714.5 mg g −1, respectively. The adsorption mechanism of Cu(ii ) on the WP/PAM was related to ion exchange and complexation, while MB adsorption was driven by hydrogen bonding and electrostatic interaction. Besides, the WP/PAM performed well in treating simulated wastewater. The regeneration test indicated that the WP/PAM could be successfully reused after 6 cycles. This work provided an alternative choice for the recycling of WP and produced a potential adsorbent for the dye and heavy metals wastewater treatment.